Effect of solvent type on solution synthesis of Na3V2(PO4)3/C cathode material for Na storage - R. Talei; S.M. Masoudpanah; M. Hasheminiasari; H. Nasrinpour (Electrochemistry Communications)
Na3V2(PO4)3/C powders were prepared using a solution technique with cetyltrimethylammonium bromide (CTAB) in various solvents, including ethanol, methanol, and glycerol. The impact of the solvent choice on the structural, microstructural, and electrochemical properties was elucidated by X-ray diffractometry, Raman spectroscopy, electron microscopy, galvanostatic charge-discharge, and electrochemical impedance spectroscopy methods. Single-phase Na3V2(PO4)3 (NVP) powders were achieved by calcining at 850 °C for 6 h, irrespective of the solvent type. Decomposition of the CTAB agent resulted in a carbon layer over the nearly spherical NVP particles. The methanol solvent revealed a finer particle size, leading to superior electrochemical performance, such as a capacity retention of 82 % after 50 cycles at a 1C current rate and a rate capability of 71.63 % when increasing the current rate from 0.1C to 1C. The superior quality carbon layer on the NVP particles, achieved by the methanol solvent, played a key role in the enhanced electrochemical performance.